1990
DOI: 10.1002/mrc.1260281114
|View full text |Cite
|
Sign up to set email alerts
|

Study of solvent effects on the nitrogen NMR shieldings of some indolizines

Abstract: Solvent effects on the nitrogen NMR shieldings of indolizine and three azaindolizines are presented for a range of thirteen solvents. The results are discussed in terms of hydrogen-bonding an solvent polarity effects. 'Pyridine-type' nitrogen atoms show a much larger range of solvent effects than do 'pyrrole-type' nitrogens; solvent to solute hydrogen bonding is the dominant contribution to the changes in shielding for the 'pyridine-type' nitrogen atoms as the solvent is varied. Solvent polarity effects are im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…As shown in Table 1 the effects of solvents on the nitrogen shieldings of means of Eq. [1] . As shown in Table 3, the s term, which represents the response of the nitrogen shielding to the oxazole and oxadiazole systems are significant and range changes in solvent polarity, reveals that more-polar sol-tems currently studied, which in principle is more electron attracting than the pyrrole-type nitrogen atoms contained vents result in a significant increase in the solute nitrogen shielding, by up to about 9 ppm on the shielding scale.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…As shown in Table 1 the effects of solvents on the nitrogen shieldings of means of Eq. [1] . As shown in Table 3, the s term, which represents the response of the nitrogen shielding to the oxazole and oxadiazole systems are significant and range changes in solvent polarity, reveals that more-polar sol-tems currently studied, which in principle is more electron attracting than the pyrrole-type nitrogen atoms contained vents result in a significant increase in the solute nitrogen shielding, by up to about 9 ppm on the shielding scale.…”
Section: Resultsmentioning
confidence: 95%
“…The resulting geometry is found to be planar with a reasonable approximately correspond to changes produced by the s term in Eq. [1].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…16 However, it has been shown that 15 N-NMR chemical shifts are also sensitive to hydrogen-bonding effects in solution. 17,18 Further, it has been shown that there is significant hydrogen bonding in these kinds of benzoxazine compounds. 19 However, in solid-state NMR, it is expected that hydrogen bonding may shift resonances only slightly, but, more importantly, may lead to an increased line width.…”
Section: Discussionmentioning
confidence: 98%
“…11) [52] experience rather limited solvent effects, up to 2 ppm, as compared to their pyridine-type nitrogen (N1 to N3) that alters its chemical shift up to 30 ppm upon changing the solvent (Table 3), similar to pyridine (44). Accordingly, N1, N2 and N3 of 55-57 may interact with hydrogen bond donor solvents, as reflected by their large and positive term a ( Table 2).…”
Section: Five-membered Azaheterocycles Azoles and Ring Fused Azolesmentioning
confidence: 93%